El control interno y su relación con el sistema de ventas y cobranzas en la empresa Double Coin, cantón Quevedo periodo 2012. - Ochoa Molina, Delia Monserrate (2015)
The relevance of heart control is a consistent contribution by the management, due to the significance of strategies to induce in the business, is to perform an evaluation of internal control in order to study the results of operations in relation to sales and collections in the importing Double Coin and in this particular way, determine how it affects their liquidity. When you run this investigation is presented as General Objective: To evaluate the incidence of internal control system sales and collection company Double Coin, period 2012 and as specific objectives Identify the performance of human resources in sales operations and collection; Apply tools for assessing internal control to establish the level of compliance; Assess the level of efficiency and effectiveness in sales operations and collection; Issue a report based on the findings detected for proper decision making. The theoretical framework of the research will be composed of the subsequent: Theoretical Foundations based on the Heart Control, Conceptual Foundations, and Legal Foundations work demonstrating sustained results. This research work has been prepared by methods that undoubtedly contributed the steps for its creation which were: Sources, Monitoring, Tracking, COSO II Method, flowcharts, narratives, Creating auditing firm, descriptive and explanatory research, no experimental design population and sample budget and the analysis and interpretation of results. In addition the results of this research work regarding the assessment of internal control in the area of sales and collections will determine the effects found and implementation integrates the work will be reflected in the accompanying report with conclusions and to this in turn you are allowed to the sound recommendations and solve the problems of the Importer.